2016
DOI: 10.1371/journal.pntd.0005057
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin Is Upregulated in Human and Murine Acute Schistosomiasis Mansoni

Abstract: BackgroundSymptomatic acute schistosomiasis mansoni is a systemic hypersensitivity reaction against the migrating schistosomula and mature eggs after a primary infection. The mechanisms involved in the pathogenesis of acute schistosomiasis are not fully elucidated. Osteopontin has been implicated in granulomatous reactions and in acute hepatic injury. Our aims were to evaluate if osteopontin plays a role in acute Schistosoma mansoni infection in both human and experimentally infected mice and if circulating OP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…Such a discrepancy in results between studies could be due to the use of OPN ELISA kits from different manufacturers, or because of different ethnicities in the study populations. Studies using ELISA kits from the same manufacturer as in this study present OPN plasma concentrations in healthy adults similar to ours [ 49 , 51 , 52 ]. Additionally, we included a small set of Swedish samples, and these results indicate that there is no difference in OPN concentration depending on ethnicity/country of residence or sex, but the cohort was small and not aged-matched, hence the results must be interpreted with caution.…”
Section: Discussionsupporting
confidence: 70%
“…Such a discrepancy in results between studies could be due to the use of OPN ELISA kits from different manufacturers, or because of different ethnicities in the study populations. Studies using ELISA kits from the same manufacturer as in this study present OPN plasma concentrations in healthy adults similar to ours [ 49 , 51 , 52 ]. Additionally, we included a small set of Swedish samples, and these results indicate that there is no difference in OPN concentration depending on ethnicity/country of residence or sex, but the cohort was small and not aged-matched, hence the results must be interpreted with caution.…”
Section: Discussionsupporting
confidence: 70%
“…In fact, Syn et al elegantly demonstrated that the pro-fibrogenic effects induced by the Hedgehog pathway are mediated by a secreted host phosphoprotein, osteopontin ( 93 ). This is substantiated by the observation that high osteopontin level in serum and liver tissue correlates with hepatic fibrosis during schistosome infection ( 65 , 66 ). This correlation was further validated in mechanistic chronic murine schistosomiasis model where higher levels of osteopontin release by macrophages associated with hepatosplenic disease ( 65 , 66 ).…”
Section: Humans Factors Associated With Liver Fibrosis During Schistomentioning
confidence: 83%
“…This is substantiated by the observation that high osteopontin level in serum and liver tissue correlates with hepatic fibrosis during schistosome infection ( 65 , 66 ). This correlation was further validated in mechanistic chronic murine schistosomiasis model where higher levels of osteopontin release by macrophages associated with hepatosplenic disease ( 65 , 66 ). Fundamentally, these findings are consistent with the demonstrated role of osteopontin in inflammation, immunity, angiogenesis, fibrogenesis and carcinogenesis in various tissues ( 94 ).…”
Section: Humans Factors Associated With Liver Fibrosis During Schistomentioning
confidence: 83%
“…Most reports have been concerned with the detection of host markers in the blood stream as an indicator of tissue damage caused by eggs (e.g. Pereira et al 2016). The CAA and CCA glycoproteins were the first secretome products identified and then developed for diagnostic puroposes.…”
Section: Secreted Schistosome Proteins As Potential New Diagnosticsmentioning
confidence: 99%